2009
DOI: 10.1038/nphys1247
|View full text |Cite
|
Sign up to set email alerts
|

Electron–nuclear interaction in 13C nanotube double quantum dots

Abstract: ). Electron-nuclear interaction in 13C nanotube double quantum dots. Nature Physics, 5(5), 321-326. https://doi.org

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
242
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(268 citation statements)
references
References 30 publications
18
242
2
3
Order By: Relevance
“…Nevertheless, spin blockade has been observed previously in carbon nanotubes [10,11,13]. In the spin blockade regime, transitions between a (1,1) and (0,2) charge state directly depend on whether the (1,1) state is a singlet or triplet.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, spin blockade has been observed previously in carbon nanotubes [10,11,13]. In the spin blockade regime, transitions between a (1,1) and (0,2) charge state directly depend on whether the (1,1) state is a singlet or triplet.…”
mentioning
confidence: 87%
“…Our measurements thus present a first quantitative analysis of the complex admittance of a double quantum dot. The demonstrated technique also provides the basis for a simple and fast detection scheme for charge and spin state readout in carbon nanotubes -a material with considerable potential for spin-based quantum information processing [8][9][10][11][12][13] -without the need for a separate charge detector [14].…”
mentioning
confidence: 99%
“…15 Recent experiments have shown that it is indeed possible to confine electrons in single [16][17][18][19] and double QDs ͑DQDs͒ in a CNT by means of electrostatic gates in cleanly grown small band-gap nanotubes. 5,15,20 The present study is motivated by these experimental results.…”
Section: Introductionmentioning
confidence: 95%
“…Spin qubits in carbon nanotubes 3,4 ͑CNTs͒ are believed to be even more robust due to the absence of hyperfine coupling in 12 C. 5 This is in contrast to GaAs QDs where the phase coherence suffers from hyperfine coupling due to the nuclei of the host crystal. However, CNTs pose other challenges and complications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several experiments have shown coherent manipulation of such spins for the purpose of spin-based quantum computation. [4][5][6][7][8][9][10] Enabled by advances in device technology, the number of quantum dots that can be accessed is quickly increasing from very few to many. 11,12 Up to date, all these quantum dots have been tuned by "hand."…”
mentioning
confidence: 99%